Dampatīdharmāmbhonidhikāvyam : sānvayam Gurjarabhāṣāṭikopetam - Someśvara (Son of Raghunātha) (Someśvara Raghunātha Bhaṭṭa, 1912)
Sanskrit text, with Gujarati translation on the code of conduct, duties and relations of married people.